1983
DOI: 10.1002/app.1983.070281023
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state polymerization of poly(ethylene terephthalate)

Abstract: Solid-state low molecular temperature. Synopsispolymerization of poly(ethy1ene terephthalate) (PET) is carried out by heating the weight prepolymer at temperatures below its melting point but above its glass transition Postcondensation occurs and the condensation byproducts can be removed by applying vacuum or inert gas. Polymers obtained usually have high molecular weight, low carboxyl and acetaldehyde content, and can be used for beverage bottle or industrial yarns. Polyesters for textile purposes are manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 12 publications
0
30
0
1
Order By: Relevance
“…Since the reaction temperature is below the melting point (SPP), the chips do not fully sinter together and the lower reaction temperature constrains degradation reactions. The polymerization rates are here higher due to the shorter diffusion path in smaller particles [31,32]. It was found that the rate of SSP increases with increase of catalyst concentration within the range 0-100 ppm Sb in starting chips [18].…”
Section: Pet Fibersmentioning
confidence: 90%
“…Since the reaction temperature is below the melting point (SPP), the chips do not fully sinter together and the lower reaction temperature constrains degradation reactions. The polymerization rates are here higher due to the shorter diffusion path in smaller particles [31,32]. It was found that the rate of SSP increases with increase of catalyst concentration within the range 0-100 ppm Sb in starting chips [18].…”
Section: Pet Fibersmentioning
confidence: 90%
“…It was reported SSP is controlled by diffusion when the PET particle size is greater than 100 mesh and the temperature is higher than 210°C whilst at a lower temperature (l 60°C) the reaction becomes the rate-controlling step. 2 In the temperature range of 160-210°C, SSP is controlled by both diffusion and reaction. However, it is clear that even above 210°C the reactions can not be totally neglected since 220 reversible condensation reactions are not at equilibrium at any instance due to the deficiency of byproducts.…”
Section: Factors Affecting Sspmentioning
confidence: 99%
“…These effects could be emphasized the higher polymer diffusivity inside the polymer matrix, i.e., the higher the process temperature for the same geometry (thickness=radius) of the reacting particles and the same initial ratio of hydroxyl to carboxyl end groups of PET flakes [12,[18][19][20][21][22] . Additionally, the reduced rate of increase in [g] at 230 C should be related to side reactions effects [23] and to the thermal behavior of the samples utilized, which exhibited a large range of crystals fusion temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%